An Assessment of Chromium (VI) Removal from Aqueous Solution Using Gelatin/PAAm-based IPN Hydrogels - Gülen Oytun Akalın (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2023)
In this work, gelatin (G)-polyacrylamide (PAAm)-based interpenetrating polymer network (IPN) hydrogels involving maleic acid (MA) was prepared using by radical polymerization. Full-IPN and semi-IPN hydrogels were synthesized by using glutaraldehyde and ethylene glycol dimethacrylate (EGDMA) as a crosslinker. The water absorbency of hydrogels was investigated, and the values increased with MA and G. The chemical structures of full-IPN and semi-IPN hydrogels were tested by Fourier Transform Infrared Spectroscopy (FTIR). Morphological test was done by using Scanning Electron Microscope/ Energy Dispersive X-ray Spectroscopy (SEM/EDX). Thermal properties were examined with Differential scanning calorimeter (DSC) analyzer and Thermogravimetric analysis (TGA). The mechanical analysis was performed with Zwick Universal Testing Machine. Thermal and mechanical stabilities of full-IPN hydrogel was higher than semi-IPN. The efficiency of adsorption parameters (contact time, initial feed concentration, and pH) on Chromium (VI) ion adsorbing property of Full-IPN hydrogel was also determined. Isotherms were explained with the Langmuir or Freundlich equations. According to the results of both isotherms, it can be said that the hydrogel surface was homogeneous, and the adsorption of Chromium (VI) occurred in a monolayer.